TOWARD A GENERAL THEORY OF CONSUMER MOTIVATION : A CRITICAL REVIEW - Bilson Simamora (Journal of Business Studies and Management Review, 2021)
Consumer motivation has been known long as a marketing concept. However, most of its concepts belong to other fields, and there is little effort to define and model them. This study aims to redefine it and develop its model. Therefore, the author narrates the history of consumer motivation and critically offers its new definition and its loose and unstructured model through which the more specific models can depart. This study found that the motivation theory goes into a more diverse direction caused by the distinctive nature of consumer behavior nature and context. For that reason, the consumer motivation model should give the spaces in which a specific model for particular behavior can be developed. The study’s loose and unstructured model is found as able to take that function. Further studies can utilize this model in studying motivation to perform or not perform particular consumption behavior in a specific context.